PENGARUH KOMPETENSI KOMUNIKASI, KECERDASAN EMOSIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PERSONEL POLSEK KEDUNDUNG KABUPATEN SAMPANG - jurnalmap map; Ali Sibro Mulisi; Nugroho Mardi Wibowo (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
This research was conducted at the Kedungdung Polsek Sampang Regency with a total sample of 33 people. This purpose is to identify and describe the communication competence, emotional intelligence, organizational culture and performance of the Kedungdung Police, Sampang Regency. Furthermore, to read and analyze the governance of communication, emotional intelligence and organizational culture, both simultaneously have an effect on the performance of the Kedungdung Police, Sampang Regency. The results showed that simultaneously, communication intelligence, intelligence and organizational culture had a very significant influence on employee performance. Partially, communication competence, emotional intelligence and organizational organization have a significant influence on the personnel performance of the Kedungdung Police, Sampang Regency. Organizational culture has a dominant influence in influencing the performance of officers in the Kedungdung Police, Sampang Regency. Keywords: communication, emotional intelligence, organizational culture, personnel performance